ANALISIS PENERAPAN SISTEM INFORMASI AKADEMIK (SIAKAD) DALAM UPAYA PENINGKATAN KINERJA PELAYANAN ADMINISTRASI AKADEMIK DI UNIVERSITAS SINGAPERBANGSA KARAWANG - Absi, Ani Rahmawati; Isyanto, Puji; Sulaeman, Eman (Jurnal Manajemen dan Bisnis Kreatif, 2018)
ABSTRACT The aim of research to analyze policies, implementation, performance of academic administrative services, efforts Stakeholders in the supervision of management information systems academic administrative services, and the impact of academic information system (SIAKAD) in an effort to improve the performance of the academic administration at the University Singaperbangsa Karawang. The thesis is expected to contribute to the bearers of economics in particular; application of academic information system (SIAKAD), Human Resource Management, Information Systems Management, and economics in general. This study uses a qualitative approach to data collection techniques are observation, interviews and in-depth interviews. The results were analyzed by comparing answers interviews with expert informants Judgment and create Conclusions and Recommendations. From the analysis of research data, be concluded as follows: 1) Policy management Singaperbangsa University Karawang already exists and has been referred to the Higher Education regulations only require better oversight again. 2) University Singaperbangsa Karawang already implementing integrated SIAKAD but still partial. 3) Performance of academic administrative services at the University of Singaperbangsa Karawang good enough after their SIAKAD. 4) Efforts Stakeholders in the supervision of the University Singaperbangsa SIAKAD in Karawang enough and needs to be increased again. 5) The impact of the application of SIAKAD enough to affect the performance of academic administrative services at the University Singaperbangsa Karawang. Furthermore, the sustainability of recommendation; SOP has been given by the Higher Education dilakuka timely and well as impact on the Quality of Higher Education. Network of SIAKAD needs to be improved. Rules Regulations of Higher Education also greatly affect the performance improvement of the service provider and academic administration. About Integration of reporting systems in each Prodi needs to be implemented immediately. Hopefully, by the Decree of the Rector of the University of Singaperbangsa Karawang to consider remuneration as a reward from the important task. Keywords: Application, Academic Information Systems, Service Performance.